1 V Electronically Tunable Differential Difference Current Conveyors Using Multiple-Input Operational Transconductance Amplifiers - Montree Kumngern; Fabian Khateb; Tomasz Kulej; Lukáš Langhammer (Sensors, 2024)
This paper presents electronically tunable current conveyors using low-voltage, low-power, multiple-input operational transconductance amplifiers (MI-OTAs). The MI-OTA is realized using the multiple-input bulk-driven Metal Oxide Semiconductor transistor (MIBD-MOST) technique to achieve minimum power consumption. The MI-OTA also features high linearity, a wide input range, and a simple Complementary Metal Oxide Semiconductor (CMOS). Thus, high-performance electronically tunable current conveyors are obtained. With the MI-OTA-based current conveyor, both an electronically tunable differential difference current conveyor (EDDCC) and a second-generation electronically tunable current conveyor (ECCII) are available. Unlike the conventional differential difference current conveyor (DDCC) and second-generation current conveyor (CCII), the current gains of the EDDCC and ECCII can be controlled by adjusting the transconductance ratio of the current conveyors. The proposed EDDCC has been used to realize a voltage-to-current converter and current-mode universal filter to show the advantages of the current gain of the EDDCC. The proposed current conveyors and their applications are designed and simulated in the Cadence environment using 0.18 μm TSMC (Taiwan Semiconductor Manufacturing Company) CMOS technology. The proposed circuit uses ±0.5 V of power supply and consumes 90 μW of power. The simulation results are presented and confirm the functionality of the proposed circuit and the filter application. Furthermore, the experimental measurement of the EDDCC implemented in the form of a breadboard connection using a commercially available LM13700 device is presented.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in Semiconductor Devices and Circuit Design; Neuroscience and Neural Engineering